Summer of Love : Psychedelische Kunst der 60er Jahre - Austin, Joe; Curtis, Barry; Diederichsen, Diedrich; Feuerstein, Günther; Grunenberg, Christoph; Hickey, Dave; Hollein, Max; Husslein, Uwe; Iles, Chrissie; Matt, Gerald; Miles, Barry; Mittringer, Markus; et al. (Frankfurt Liverpool Ostfildern-Ruit Wien : Hatje Cantz Verlag Ostfildern-Ruit Kunsthalle Wien Schirn Kunsthalle Frankfurt Tate Liverpool, 2005)
Abrams, Isaac ; Abrams, Jerry ; Agnew, Dan ; Alotta, Albert ; Ant Farm ; Archigram ; Aubert, Jean ; Bayrle, Thomas ; Beek, Stan Van der ; Belson, Jordan ; Benglis, Lynda ; Boyle, Mark ; Brummbär & Knollfick ; Buckminster Fuller, Richard ; Cohen, Bernard ; Cohen, Ira ; Döring, Wolfgang ; Fahlström, Öyvind ; Hamilton, Richard ; Haus-Rucker-Co ; Hendrix, Jimi ; Hills, Joan ; Hindle, Will ; de Hirsch, Storm ; Hirsh, Hy ; Hollein, Hans ; Jenkins, Paul ; Jordan, Lawrence ; Kauffman, Craig ; Klarwein, Mati ; Kriwet, Ferdinand ; Kusama Yayoi ; Levine, Charles ; Lindner, Richard ; Lipton, Lenny ; McCracken, John ; McKay's Headlights, Glenn ; Metzger, Gustav ; Nameth, Ronald ; O'Neill, Pat ; Paik, Nam June ; Palatnik, Abraham ; Panton, Verner ; Parc, Julio Le ; Pinter, Klaus ; Piper, Adrian ; Samaras, Lucas ; Schoffer, Nicolas ; Sedgley, Peter ; Shimizu, Akira ; Stehura, John ; Stevens, Graham ; Warhol, Andy ; White, Joshua ; Whitney, James ; Wilfred, Thomas ; Wimmenauer, Karl ; Wyndham, Chas ; Yalkut, Jud ; Young, La Monte ; Zazeela, Marian
Duits
boek